TOXICITY PROFILES OF METHANOL EXTRACT OF CROSSOPTERYX FEBRIFUGA LEAF (AFZEL. EX G. DON) BENTH - Isah, A. O.; Idu, M.; Amaechina, F. C. (FUDMA JOURNAL OF SCIENCES, 2023)
Crossopteryx febrifuga is one of the plants used for the local treatment of some disease conditions by the people of Nigeria via its leaf, root and bark without knowing the toxic nature of the plant recipes. This research was designed to ascertain the toxicity profiles of the plant leaf. Acute toxicity was determined in two phases using rats. In sub-acute toxicity studies, haematology, histopathology and evaluation of liver function indices were conducted. In the first phase of the toxicity study, the mice showed no observable toxic effects as high as at 1000 mg/kg. However, it caused sluggishness, respiratory distress at higher doses in the second phase. On haematological indices, white blood cell, lymphocyte, erythrocytes, haemoglobin, haematocrit rose significantly across the doses administered. The liver function test revealed significant increase in serum alkaline phosphatase (ALP), alanine transaminase (ALT), aspartate transaminase (AST), albumin, total protein and conjugated bilirubin while 800 mg/kg extract reduced the aspartate transaminase. On histopathology, liver revealed normal hepatocytes but dilated central vein while in kidney, renal corpuscle, glomeruli and tubule were normal. On heart, revealed was active vascular congestion with normal bundle of myocardial fibres and coronary artery while in aorta, it revealed normal architecture. With the nature of the toxicity profile revealed especially at doses less than 500 mg/kg of C. febrifuga extract, the plant could be considered to be relatively safe. This study is significant as it provides information that may suggest some safe doses out of the doses used for clinical trial and application